Synthesis and Kinetics of Highly Substituted Piperidines in the Presence of Tartaric Acid as a Catalyst - Ghalandarzehi, Younes; Shahraki, Mehdi; Habibi-Khorassani, Sayyed M. (Combinatorial Chemistry & High Throughput Screening, 2018)
Aim & Scope: The synthesis of highly substituted piperidine from the one-pot reaction between aromatic aldehydes, anilines and β-ketoesters in the presence of tartaric acid as a catalyst has been investigated in both methanol and ethanol media at ambient temperature. Different conditions of temperature and solvent were employed for calculating the thermodynamic parameters and obtaining an experimental approach to the kinetics and mechanism. Experiments were carried out under different temperature and solvent conditions. Material and Methods: Products were characterized by comparison of physical data with authentic samples and spectroscopic data (IR and NMR). Rate constants are presented as an average of several kinetic runs (at least 6-10) and are reproducible within ± 3%. The overall rate of reaction is followed by monitoring the absorbance changes of the products versus time on a Varian (Model Cary Bio- 300) UV-vis spectrophotometer with a 10 mm light-path cell. Results: The best result was achieved in the presence of 0.075 g (0.1 M) of catalyst and 5 mL methanol at ambient temperature. When the reaction was carried out under solvent-free conditions, the product was obtained in a moderate yield (25%). Methanol was optimized as a desirable solvent in the synthesis of piperidine, nevertheless, ethanol in a kinetic investigation had none effect on the enhancement of the reaction rate than methanol. Based on the spectral data, the overall order of the reaction followed the second order kinetics. The results showed that the first step of the reaction mechanism is a rate determining step. Conclusion: The use of tartaric acid has many advantages such as mild reaction conditions, simple and readily available precursors and inexpensive catalyst. The proposed mechanism was confirmed by experimental results and a steady state approximation.
Keywords: Piperidine